Perbandingan metode double exponential smoothing holt dan trend analysis untuk memprediksi penjualan minuman kopi - Sinta Nasmia Lizahrotu Alifah; Gerry Sastro (Papanda Journal of Mathematics and Science Research, 2026)
This study aims to identify and compare the most effective forecasting methods in predicting coffee beverage sales in minimarkets using Holt's Double Exponential Smoothing and Trend Analysis methods. The main problem in this study is to determine the forecasting method that can provide the highest level of accuracy to support optimal inventory planning. This research was conducted at a minimarket, namely Indomaret TangCity, as the research location, using secondary data in the form of monthly coffee beverage sales data from January 2022 to June 2025. This research did not involve participants directly but focused on historical sales data as the object of analysis. The research method used was a quantitative approach with a comparative method. The data was analyzed using Holt's Double Exponential Smoothing and Trend Analysis methods, which are suitable for data with trend patterns. The analysis stages included determining the smoothing parameters, calculating the forecasting results, and evaluating the accuracy using the Mean Square Error (MSE), Mean Absolute Deviation (MAD), and Mean Absolute Percentage Error (MAPE) measures. The results show that the Quadratic Trend Analysis method has the best accuracy with an MSE value of 87,337.41, MAD of 224.37, and MAPE of 7.247%. Therefore, this method is used to forecast coffee beverage sales for the period July 2025 to December 2025.